La tradición clásica en La Regenta de Leopoldo Alas, «Clarín» - López Férez, Juan Antonio (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2010)
Leopoldo Alas, «Clarín», often mentions the Graeco- Roman classics, sometimes with satyrical intention, demonstrating the ignorance or bad use of the Graeco- Roman tradition in his time. I examine the presence of this tradition in La Regenta (1884-1885), distributing the material in several items: quotations and Latin phrases; observations about the knowledge or ignorance of Greek or Latin; mentions of authors or works from Greek literature; direct references of authors or works of Latin literature; Greek or Roman historical personages; notes of Graeco- Roman culture; indication about the Greek or Latin vocabulary.